Bioactive Phenolic Compounds in Extra Virgin Olive Oil: Implications for Cardiovascular Health - Vázquez-Jiménez, Cristina; Rodríguez-Pérez, María Dolores; Ortega-Hombrados, Laura; Sánchez-Tévar, Ana María; De-la-Cruz-Cortés, José Pedro; González-Correa, José Antonio (Wiley, 2026)
Polyphenols, bioactive compounds abundant in plant-based foods, have attracted significant interest for their potential cardio-vascular benefits. This narrative review summarizes the current evidence on how polyphenols contained in extra virgin oliveoil impact cardiovascular health, including their molecular mechanisms of action and clinical effects. Polyphenols exert anti-oxidant and anti-inflammatory effects in vascular cells by modulating key signaling pathways (e.g., NF-κB, Nrf2, and PI3K/Akt) and activating endothelial nitric oxide production, which collectively may improve endothelial function and reduce ather-osclerotic burden. We review human trials of polyphenol-rich foods (such as berries, cocoa, tea, and wine) and isolated polyphe-nol supplements, which generally report improvements in blood pressure, vascular function, lipid profiles, and inflammatorymarkers—though results are not uniform. Limitations of these trials (small sample sizes, short durations) and variability inindividual responses are discussed. We also consider the role of polyphenol metabolism and bioavailability, noting that gutmicrobiota–derived metabolites (e.g., urolithins, equol) likely contribute to the cardioprotective effects. Overall, a diet rich indiverse polyphenols appears to confer cardiovascular benefits, but more personalized research is needed to define optimal typesand doses for specific patient profiles. Practical recommendations for incorporating polyphenol-rich foods into cardiovascularprevention strategies are provided.
Keywords: Polifenoles; Aceite de oliva; Polyphenols; extra virgin olive oil